Research of Emotional Intelligence as a Psychological Resource of an Athlete - Tetiana Petrovska; Nataliia Kulish; Viktor Kostiukevych; Ruslana Sluhenska; Nataliia Reshetilova; Alyona Yerokhova (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2021)
Emotional intelligence (EI) is an important part of the psychology of an athlete and must be considered when a training programme is being devised. The aim of this research is to determine the impact of physical activity on the EI level among youth; examine the extent to which EI and sports achievements is correlated; consider the discrepancies between EI indicators within athletes in different sport disciplines. The EI of 245 young people aged 17-19 was studied. 125 of them were athletes who were systematically engaged in sports and competitions for 3½ years. The remaining 120 were not engaged in any sport. The research is based on the methodology that Nel- son-Hall devised to assess EI. It also uses various methods of mathematical statistical analysis, such as Student's t-test. The extent of the EI in young athletes was significantly higher than that in their peers who had not done any sports. In a group of athletes differences were found in EI components between athletes of different sport disciplines. This was shown in the indices of emotional management, self-motivation and in the extent to which they were aware of other people's emotions. The research showed that athletes with higher levels of emotional management tend to achieve better results than those with lower emotional management abilities. It is likely that this observation will hold true for athletes from across the broad spectrum of sporting ability.